Advances in soft computing. 15th Mexican International Conference on Artificial Intelligence, MICAI 2016, Cancún, Mexico, October 23?28, 2016, Proceedings /: 15th Mexican International Conference on Artificial Intelligence, MICAI 2016, Cancún, Mexico, October 23?28, 2016, Proceedings. Part II : (2017) - Unknown
No abstract available